THE USE OF M-U-F FRAMEWORK IN IMPROVINGSTUDENTS' GRAMMATICAL COMPETENCE(A QUASI-EXPERIMENTAL RESEARCH ON A FIFTH GRADER IN AN ELEMENTARY SCHOOLIN WESTERN BANDUNG) - Devian Try Gustary, - (2010)
Most of elementary teachers use grammar translation method in teaching English. Students are asked to memorize vocabularies and the grammatical pattern without knowing the context of using it. Meanwhile, young learners need to learn English grammar in context. By giving them context, there is an obvious reason for them to learn it. This research was aimed to investigate the use of M-U-F framework in improving students' grammatical competence, and to find out the strengths and challenges of using M-U-F framework. M-U-F stands for Meaning, Use and Form. This framework assists young learners to develop their internal grammar through the opportunities to use and practice the language without neglecting the context of using it and also the pattern of the language. The research was conducted by using a quasi-experimental design with nonequivalent groups design. Two classes of fifth grade in one of the elementary school in Western Bandung were chosen as a sample. Class 5A was an experimental group and class 5B was a control group. Each of the class consists of 24 students. The result indicated that there was not a significant effect of MUF framework in improving students' grammatical competence as indicated by a statistically posttest score of experimental group students which had a better grammar test score (M = 78.54, SE = 2.32) than the control group students (M = 75.00, SE = 2.43). However, the difference was not highly significant t (46) = 1.055, p < 0.05 with the effect size value r = 0.15. The findings from video recording showed that the meaningful context, purposeful and interesting activity that make students use the language and aware of its form became the strengths of M-U-F framework. Besides, the class management and limitation of time were the challenges of using M-U-F framework. The main conclusion that can be drawn from the research was that M-U-F Framework did not significantly improve students' grammatical competence. However, it could encourage learners to learn English grammar in meaningful and interesting ways. As the suggestions, for teachers who are interested in using M-U-F framework, it is suggested to build the context which is familiar with the students. While for the further researchers, it is suggested to conduct the research in a long period of time.